The importance of having nuclear power technologies for sustainable energy development - Yüksel, Serhat; Çağlayan, Çağatay; Mikhaylov, Alexey (Springer Science and Business Media Deutschland GmbH, 2023)
Having nuclear energy technologies is vital for countries’ energy policies to be sustainable. In this context, countries need to pay attention to some issues to have these technologies. In this context, the necessary budget should be allocated for research and development studies. Secondly, qualified personnel must also be employed. Thanks to these personnel, it will be possible to operate nuclear power plants with complex processes in a safer way. Third, government incentives are also important for the development of these technologies. Finally, the economic growth of countries is another important issue in this context. In other words, to have up-to-date technologies related to nuclear energy, countries must first be economically developed. Priority analysis of these four different factors will be made under this heading. In this process, the DEMATEL method will be considered. It is determined that economic development is the key factor for the purpose of improving nuclear energy technologies. Research and development studies also have a significant role in this respect. Qualified personnel and government incentives are in the last ranks. The results obtained from this study show us that for the development of nuclear energy technologies, countries must first grow their economies. In other words, countries with underdeveloped economies will not be able to find the necessary budget for nuclear energy technologies. In this case, the necessary research and development studies for these current technologies will not be able to be carried out.
Keywords: DEMATEL; Energy Economics; Energy Investments; Nuclear Energy; Sustainable Energy